Global research trends of Hindu Studies– through the lens of Web of Science database - Navaneethakrishnan, S. (University of Jaffna, 2022)
Hindu studies is the study of the traditions and practices of the Indian subcontinent, especially Hindu culture related to religion, languages, literature, philosophy, history, arts and society, in all periods and in all parts of the world. Due to insufficient awareness of Hindu studies, there is a need for the development of these research studies at global level. As such the main objective of this study was to identify global research trends of research publications related to the Hindu Studies. The research method of this study was a quantitative method especially scientometric analytical method using R-studio software and MS excel. Research publications indexed in Web of Science database up to the end of year 2020 were retrieved by using the ‘Topic terms’ as ‘Hindu" or "Hinduism" or "Hindu Studies" or "Hindu Civilization" or "Hindu Culture" for analytical purpose. There were a total of 4563publicationsincluding all types of documents published from the year 2001 to 2020.The analysis of the total 4563 publications reveals that the entire publications were contributed by 7480 authors affiliated to 2646 institutions. Journal articles occupied predominant position sharing 73% (n = 3341) percent of total study data. Research growth of publications was increased with positive indicators. In respect to the country productivity, the leading role in Hindu research was United States and it was followed by India.Journals namely South Asia-journal of South Asian studies, International journal of Hindu studies, Journal of Asian studies were given priority to publish the research findings.Among the keywords used in these publications ‘hindukush’, ‘hindu nationalism’, and ‘south india’ were given priority. This study recommends publishing more research articles on Hindu studies at international level to increase the research productivity and to take measures to improve the international visibilityof Sri Lankan authors.
Keywords: Hindu Studies; Hinduism; Web of Science; Research trends